SEASONAL SCREENING OF THE MYCOTIC INFECTIONS OF CULTURED FRESHWATER FISHES IN KAFR EL-SHEIKH GOVERNORATE - Nadia Mahfouz; Eman Moustafa; Mohamed Kassab; Wesam Marzouk (Slovenian Veterinary Research, 2019)
The present study was carried out to screen the predominant mycotic infections among freshwater fishes (Oreochromis niloticus and Clarias gariepinus) in Kafrelsheikh fish farms; with special focus on the seasonal incidence; as well as, the histopathological changes induced by the detected fungi. 500 specimens of freshwater fishes (400 O. niloticus and 100 C. gariepinus) were investigated for seasonal incidence of mycotic diseases. Mycological examination revealed the isolation of 2148 fungal isolates from 375 diseased and 125 apparently healthy fish samples (1828 mould and 320 yeast isolates), of which 1258 were isolated from O. niloticus and 890 isolates from C. gariepinus. Saprolegnia was the predominant among diseased fishes with highest prevalence in late autumn (10.68%, 6.96%) and winter (6.81%, 7.87%) in O. niloticus and C. gariepinus, respectively. However, Pencillium sp. and Aspergillus sp. were the most predominant fungi isolated from apparently healthy fishes. The highest prevalence of Pencillium  sp. were recorded in winter, whileas  Aspergillus showed variations between species; Aspergillus flavus, Aspergillus niger were more prevalent in summer (25.44%, 23.22%) and  (26.9%, 37.44%) and Aspergillus terrus, Aspergillus fumigatus were more prevalent in autumn (5.98%, 5.67%) and  (7.69%, 8.23%) in O. niloticus and  C. gariepinus, respectively. Moreover, the highest prevalence of Fusarium species was recorded in spring (11.8%, 5.91%) from O. niloticus, C. gariepinus, respectively. Mucor recorded the highest prevalence in autumn (20.09%) in O. niloticus and winter (29.21%) in C. gariepinus; whileas Rhizopus was highest in summer (7.89%, 5.21%) in O. niloticus and C. gariepinus, respectively. Four genera from yeast were isolated; Candida sp. (28.44%, 36.27%), Rhodotorula sp. (36.24%, 24.51%), Cryptococcus sp. (16.97%, 20.59%) and Trichosporon Sp. (18.35%, 18.63%) in O. niloticus and C. gariepinus, respectively. The histopathological findings revealed severe degenerative changes in skin and gills with presence of fungal hyphae and spores.